Professional Activation and Social Integration from the Perspective of the Social Economy Sector in Poland: the Example of Social Integration Centres - Łojko, Majka (Olsztyn Economic Journal, 2022)
This paper examines the role and responsibilities of the social economy (SE) in Poland in promoting social and professional integration for individuals at risk of exclusion. It specifically focuses on Social Integration Centres as an example. The central argument is that these centres play a crucial role in providing multi-level support to at-risk individuals, enabling them to achieve social and professional integration. The paper provides an overview of the topic, drawing conclusions from relevant literature, data from Statistics Poland, reports from the Ministry of Family, Labour and Social Policy, and scientific studies related to the social economy. The analysis shows that Social Integration Centres in Poland assist in the restoration and enhancement of the abilities of those who are socially excluded to enable them to perform social and professional roles independently. They implement multifaceted reintegration efforts, helping individuals to acquire the necessary skills to reengage in professional and social activities.